PENDUGAAN PERKEMBANGAN POPULASI ORYCTES RHINOCEROS L. (COLEOPTERA: SCARABAEIDAE) DI PERKEBUNAN KELAPA SAWIT (ELAEIS GUINEENSIS JACQ.) - Pujiastuti., dkk, Yulia (Jurnal Rekayasa Lingkungan)
Approximately 1.000 species of insects are associated with coconut worldwide. Over 40 species of coleopteran pests have been recorded ? most are under effective natural control but some require interventions. In view of the increasing and devastating damage by coconut beetle (Oryctes rhinoceros) to coconut palms in the many countries, many efforts are made to find appropriate method to forecast its population. The basic procedures of these monitoring programs are outlined together with forecasting method. A study to forecast coconut beetle population has been carried out in palm oil estate, near Palembang. Study was aimed to estimate population after several observations of beetle population. Another aim was to assess the influences of environmental factors, i.e. temperature, relative humidity and rainfall intensity, which could affect to the beetle population fluctuation. Results showed beetle population could 65.12 percent in average due to unsuitable environmental factors. At first observation temperature was recorded 26 ? 30 0C and 1185 larvae werefound. At last observation larvae population decreased to 392 larvae at temperature 29 ? 33 0C. It was found that relative humidity and rainfall intensity also played important role in decreasing beetle population.Keywords: coconut beetle, time series analysis, population estimation, environmentalfactors